Are consumers of Internet health information “cyberchondriacs”? Characteristics of 24,965 users of a depression screening site - Leykin, Yan (2011)
BACKGROUND: The number of individuals looking for health information on the Internet continues to expand. The purpose of the study was to understand the prevalence of major depression, among English-speaking individuals worldwide looking for information on depression online. METHODS: An automated online Mood Screener website was created and advertised via Google AdWords, for one year. Participants (N = 24,965) completed a depression screening measure and received feedback based on their results. Participants were then invited to participate in a longitudinal mood screening study. RESULTS: Of the 24,965 who completed the screening, 66.6% screened positive for current major depression, 44.4% indicated current suicidality, and 7.8% reported a recent (past two weeks) suicide attempt. Of those consenting to participate in the longitudinal study (n = 1,327, from 86 countries), 77.4% screened positive for past depression, 64.6% reported past suicidality, and 17.5% a past suicide attempt. Yet, only 25% of those screening positive for current depression, and only 37.2% of those reporting a recent suicide attempt are in treatment. CONCLUSIONS: Many of the consumers of Internet health information may genuinely need treatment and are not “cyberchondriacs”. Online screening, treatment, and prevention efforts may have the potential to serve many currently untreated clinically depressed and suicidal individuals.